Factores etiológicos de la discalculia - Mendoza Macías, María Angélica (My University, 2020)
The following essay presents the etiology of dyscalculia, this word refers to the learning difficulty in the logical mathematical area. First, concepts given by various authors about learning will be given based on a cognitive-behavioral perspective, Through a bibliographic research and taking the descriptive qualitative method, it continues with the specific learning problems such as dysgraphia, dyslexia and the central theme of the essay, dyscalculia conceptualizing, exploring its etiology where the specific cause is not clarified However, there are studies showing that there are abnormalities in different areas of the brain, it is also mentioned that there are cognitive factors, possible hereditary genes due to the presence of one or more relatives with the disorder and environmental factors that influence this learning problem. The classification affirmed by Kosc is mentioned, in addition the signs and symptoms according to the DSM-5 are described. Subsequently, for its correct evaluation, positions of different authors have been developed establishing the psychopedagogical strategies that can be used in which 3 important factors intervene such as parents, teachers and the student, in the same way, a correct clinical interview in the case of the mental health professional. Next, guidelines for treatment were developed, identifying that the educational area intervenes in a way and that several authors state that the change or improvement of this difficulty is done through a 180 degree turn within the educational classroom, however, parents influence and contribute to this learning and the respective conclusions.
El siguiente ensayo presenta la etiología de la discalculia, dicha palabra hace referencia a la dificultad de aprendizaje en el área lógico matemático. Primero se dará conceptos dados por varios autores sobre aprendizaje basándose en una perspectiva cognitivo-conductual,a través de una investigación bibliográfica y tomando el método cualitativo descriptivo, se prosigue con los problemas de aprendizaje específico como lo son disgrafía, dislexia y el tema central del ensayo, la discalculia conceptualizando, explorando su etiología donde no se clarifica la causa específica sin embargo, hay estudios manifestando que existen anomalías en diferentes áreas del cerebro, también se menciona que existen factores cognoscitivos, posibles genes hereditarios por la presencia de uno o más familiares con el trastorno y factores ambientales que influyen en este problema de aprendizaje. Se menciona la clasificación afirmada por Kosc, además se describen los signos y síntomas según el DSM-5. Posteriormente, para su correcta evaluación se ha desarrollado posturas de diferentes autores estableciendo las estrategias psicopedagógicas que se pueden usar en la que intervienen 3 factores importantes como son los padres, los docentes y el estudiante; de igual forma una correcta entrevista clínica en el caso del profesional de salud mental. Seguidamente, se desarrollaron pautas para el tratamiento, identificando que el área educativa interviene sobre manera y que varios autores manifiestan que el cambio o mejora de esta dificultad se hace mediante un giro de 180 grados dentro del aula educativa, no obstante, los padres influyen y aportan en este aprendizaje y las respectivas conclusiones.
Keywords: TRASTORNO; APRENDIZAJE; ETIOLOGIA; DISCALCULIA